TINJAUAN KEBIJAKAN DESENTRALISASI PENDIDIKAN DI INDONESIA - Deding Ishak (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
In Indonesian national education, the concept of decentralization is still a relatively recent one. It has been mandated by the government in Indonesia's Education Law number 20 of 2003. It is the goal of this research to examine the strategic concerns surrounding Indonesia's education decentralization strategy and then develop alternate strategies for putting them into action. The development of decentralized education is supposed to provide more space for stakeholders. Descriptive analysis and a qualitative method are used in this investigation. Researchers found that Indonesia's main challenges in implementing education policies are in quality control, financing, and teacher professionalism. This can serve as a guide for both central and regional governments to create powerful formulas for making appropriate policies so they can improve education quality. It is impossible to apply the decentralization concept without taking into consideration political and sociological considerations.